2012
DOI: 10.2147/vhrm.s28041
|View full text |Cite
|
Sign up to set email alerts
|

The complex regulation of TGF-ß in cardiovascular disease

Abstract: Transforming growth factor β (TGF-β1) is a pleiotropic cytokine with many and complex effects in cell and tissue physiology. This is made possible by a very complex and interwoven signaling system, whose regulation continues to be the focus of a growing line of research. This complex regulation translates to a key role in cardiovascular physiology, hemostasis, and the blood–vessel interface. In accordance with this, the TGF-β1 pathway appears to be deregulated in related disorders, such as atherosclerotic vasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 86 publications
2
31
0
Order By: Relevance
“…In atherosclerosis, TGF-β1 seems to lose its atheroprotective effects [2,5]. TGF-β1 exerts its wide variety of biological actions by means of very complex signaling pathways, some of which converge in the expression of the cell cycle regulatory protein p27 [3,4].…”
Section: Discussionmentioning
confidence: 99%
“…In atherosclerosis, TGF-β1 seems to lose its atheroprotective effects [2,5]. TGF-β1 exerts its wide variety of biological actions by means of very complex signaling pathways, some of which converge in the expression of the cell cycle regulatory protein p27 [3,4].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the TGF-β family is large and has multiple effects on vascular smooth muscle and endothelial cells. Both measured elevations and reductions in TGF-β have been reported to be involved in vascular pathology [24]. …”
Section: Discussionmentioning
confidence: 99%
“…This finding remains significant after having accounted for traditional risk factors, including age and history of CVD. We and others [2,3,24,28] have shown that DKD patients as an entire cohort are at greater mortality risk than CKD of other etiologies. In addition, we now demonstrate that biomarkers associated with a variety of different vascular pathophysiological processes may aid in identifying patients within the DKD group who are at highest risk of death before dialysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent evidence suggests that the modulation of immune responses is a promising approach for the prevention and treatment of atherosclerosis . TGF‐β1 pathway has been shown to be upregulated in a variety of immune disorders, including atherosclerosis . Therefore, we hypothesized that RGS3 regulates TGF‐β1 pathway to inhibit inflammation and atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%